Tadeusz Miciński, teatr polski i Polacy w Moskwie w latach 1915-1918 (na marginesie wojennej publicystyki poety) - Sobieraj, Sławomir (Przegląd Wschodnioeuropejski, 2023)
The article analyzes the cultural life of Poles in exile in Moscow during the First World War, based on the journalism of the Polish writer T. Miciński. The article focuses on issues related to theatre and national rebirth. The research uses historical and biographical methods. The article considers two main sources. Firstly, the article analyzes memoirs of people who lived in that period. Secondly, the article looks at Miciński’s wartime journalistic texts. These texts include three of Miciński’s articles previously unknown to researchers, which were published in 1916 in the Moscow daily paper “Gazeta Polska”. The analysis has shown that Miciński’s journalism contains a lot of information about theatrical culture, and his voice in the Russian press and meetings with theatre artists could have a significant impact on the evolution of the performing arts in interwar Poland.